Selection of amplifier for optimized charge transfer in active pixel CMOS time of flight (TOF) image sensors. - Abdul Halin, Izhal; Aris, Ishak; Isa, Maryam; Shafie, Suhaidi; Kawahito, Shoji; Ud Din, Amad (2011)
Although CMOS Time-of-Flight Range Image Sensors have been recently realized, the fabrication process in modified by inserting an extra mask layer to allow efficient TOF dependent charge transfer.